Cultura(s), educação (física) e esporte (s) – nas teias de uma pesquisa-ação extensionista em uma universidade pública baiana - Barbosa, Jaderson Silva (2014)
This study was an Action Research involving an action extension, the Forward Program: Citizen Action ( PEAC ), State University of Feira de Santana, Bahia and had as its object of study, the Sports School project that cared for children from 9 to 14 years residents of neighborhoods Campo Limpo and Novo Horizonte. Research problems were jointly constructed between actors and social and directed to answer the following questions authors: what are the phenomena that influence or influenced the construction of the conception of sport stakeholders and social actors involved in the PEAC? As the PEAC in its relations involving their intervention (action research), takes a critical-reflexive appropriation of knowledge and experience of the body in culture / with sports? There PEAC contribution in sports training and civic education of the students enrolled in the School of Sport this program? A significant contribution of the PEAC, in order to allow for social change in reality in the context where the program was implemented? To answers these questions, the study proposed a critical perspective, however, without making epistemic entrenchments, using contributions of theoretical frameworks in the field of Physical Education to discuss about physical culture and sport, in addition to the discussion of university extension. The analysis of data extracted from statements made by the subjects involved in the actions of the program (families, students, teachers and scholars of the program) were tabulated, organized and described using the technique of the Collective Subject Discourse. The main results of this Action Research highlights are proposing to reorganize the teaching (and learning as a result of) the sport in higher education and in social projects, a critical perspective, using various bodily expressive possibilities in an integrative action capable of initiating paradigm shifts in educational arenas, proposing social change in reality where social actors and authors are entered and recognizing the limitations regarding the extent of the changes. Furthermore, experiments with the PEAC, especially the Sports School project , which brought elements propose disruptions and contributions in micro dimensions ( sport , physical education and his theories) and macrostructural (model of society, public policy and extension), both permanently interconnected .